HOW TEACHERS DEAL WITH INDIVIDUAL DIFFERENCES IN THE LANGUAGE CLASSROOM: RESULTS OF A STUDY - Pawlak, Mirosław (Neofilolog, 2019)
The process and outcome of second or foreign language (L2) learning are mediated by an array of variables, the most important of which are perhaps individual difference (ID) factors (cf. Dörnyei, 2005; Dörnyei, Ryan, 2015; Pawlak, 2012a, 2017a). It is therefore not surprising that such factors have been addressed by hundreds, if not thousands, of studies in the last several decades, and while the foci or methodology of such research have inevitably been subject to change, the role of individual variation in L2 has been taken for granted. Apart from illuminating the role of various ID factors, researchers have also attempted to draw up recommendations concerning how what we know about these factors can inform classroom practice. A question arises, though, about teachers’ awareness of different facets of individual variation, the steps they take to capitalize on learners’ individuality in providing instruction, and the degree to which they can be expected to successfully deal with ID factors in the classroom. The paper tackles these issues by reporting on a questionnaire study which involved 37 Polish teachers of English at different educational levels. The results indicate that, while the respondents are cognizant of individual differences and address them in teaching practice, their understanding thereof is limited and so are the actions they embark on in this respect.